The role of andrographolide as a potential anticancer agent against gastric cancer cell lines: a systematic review - Muhamad Alojid Anis Amiera; Tuan Noorkorina Tuan Kub; Azian Harun; Rohimah Mohamud; Nur Rina Alissa Razian; Yasmin Khairani Muhammad Ismadi; Wan Alif Syazwani Wan Alias; Mohammed Hussain Abdulrazak; Ernawati Teni (PeerJ)
Objective To critically analyse literature on the anticancer properties of andrographolide in in vitro studies on gastric cancer cells. Method This study systematically reviewed articles from 2013 to 2024 across five prominent databases; PubMed, Google Scholar, Web of Science, Scopus, and Science Direct, EMBASE, Cochrane library and DOAJ. The study eligibility criteria include original studies assessing using gastric cancer cell lines and articles utilizing extracted andrographolide from Andrographis paniculata or standard andrographolide source treatment. The following exclusion criteria were articles written in a different language, review articles, book chapters, conference articles, scientific reports. Duplicated articles were removed using Mendeley software. Result Out of 93 articles, six were relevant, primarily focusing on in vitro analyses with gastric adenocarcinoma cell lines. Conclusion These studies indicate that andrographolide can hinder the cell cycle, suppress cell proliferation, alleviate oxidative stress, and induce apoptosis by prompting gastric cancer cells to undergo self-destruction, which is a crucial mechanism for controlling and eliminating cancerous growths.